Finite Element Analysis of SAW Sensor with ZnO Substrate for Dichloromethane (DCM) Gas Detection - MOUSTAFA, Mohamed; LAOUINI, Ghaylen; ALZOUBI, Tariq (Archives of Acoustics, 2021)
A SAW gas sensor based on Zinc Oxide (ZnO) piezoelectric substrate is simulated and evaluated for the detection of the dichloromethane (DCM) volatile organic compound (VOC). The study is performed based on the finite element method (FEM) using COMSOL Multiphysics software. The obtained device response using the ZnO substrate is compared to the one using the typical lithium niobate (LiNbO3) piezoelectric substrate. A thin film of polyisobutylene (PIB) membrane is selected to act as the sensing layer. The obtained results reveal a linear behaviour of the resonance frequency downshift (i.e., the sensor sensitivity) versus the investigated gas concentrations varying from 10 ppm to 100 ppm of DCM gas. Additionally, the sensor response is investigated by applying several thicknesses of PIB ranging from 0.3 μm to 1.0 μm. The observed sensor response shows less dependence on the PIB thickness using the ZnO substrate than the LiNbO3 one.